Electrochemical sensor for rutin detection based on N-doped mesoporous carbon nanospheres and graphene. (1st March 2021) - Zhen, Qingfang; Ma, Huiyuan; Jin, Zhongxin; Zhu, Di; Liu, Xiao; Sun, Yu; Zhang, Chunjing; Pang, Haijun
Abstract : A new electrochemical sensor shows great sensing performance to rutin and high selectivity towards even 13 interfering species and realizes detection of rutin in real samples such as human serum. Abstract : In this work, a novel composite based on N-Doped mesoporous carbon nanospheres and graphene (N-MCS@graphene) is successfully designed and constructed for rutin (RT) detection. The ordered mesoporous architecture offers high specific surface area, and open pores that lead to amplified target/receptor interfaces and a fast diffusion path for the analyte. Meanwhile, graphene can facilitate charge transfer and provide rich active sites. Amperometry and cyclic voltammetry are used to investigate the electrochemical properties and sensing ability of a N-MCS@graphene modified electrode. The results indicate that the N-MCS@graphene electrode shows a greatly enhanced electrochemical response to RT, and possesses great sensing performance towards RT with the linear range of 0.5–189 μM, the detection limit of 0.05 μM, and favorable selectivity towards common interfering species. Moreover, the composite can be used for the determination of RT in human serum with satisfactory results.